2016
DOI: 10.1155/2016/1710561
|View full text |Cite
|
Sign up to set email alerts
|

Operator Influence on Blinded Diagnostic Accuracy of Point-of-Care Antigen Testing for Group A Streptococcal Pharyngitis

Abstract: Background. Acute pharyngitis caused by Group A Streptococcus (GAS) is a common presentation to pediatric emergency departments (ED). Diagnosis with conventional throat culture requires 18–24 hours, which prevents point-of-care treatment decisions. Rapid antigen detection tests (RADT) are faster, but previous reports demonstrate significant operator influence on performance. Objective. To measure operator influence on the diagnostic accuracy of a RADT when performed by pediatric ED nurses and clinical microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The assessment of risk of bias and applicability for the 26 included test accuracy studies 20,23,24,[34][35][36][37][38][39][40][41][42][43][44][45][46][48][49][50][51][52][55][56][57][58]69 using the QUADAS-2 tool are summarised in Table 7 and Figure 5. Four of the included studies compared two index tests that are relevant to this review, so there are 30 quality assessment ratings for the index test domains.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The assessment of risk of bias and applicability for the 26 included test accuracy studies 20,23,24,[34][35][36][37][38][39][40][41][42][43][44][45][46][48][49][50][51][52][55][56][57][58]69 using the QUADAS-2 tool are summarised in Table 7 and Figure 5. Four of the included studies compared two index tests that are relevant to this review, so there are 30 quality assessment ratings for the index test domains.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 29 studies (full texts and abstracts) 6,20,23,24, identified by the search, 26 of the studies reported test accuracy data. 20,23,24,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]54,57,58,63 Three of the identified studies 6,53,55 reported only other outcomes (such as antibiotic-prescribing rates) and did not report test accuracy.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations